2004
DOI: 10.1016/s0006-3495(04)74224-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Structural Changes in the Lipid Bilayer upon Insertion of the Transmembrane Domain of the Membrane-Bound Protein Phospholamban Utilizing 31P and 2H Solid-State NMR Spectroscopy

Abstract: Phospholamban (PLB) is a 52-amino acid integral membrane protein that regulates the flow of Ca(2+) ions in cardiac muscle cells. In the present study, the transmembrane domain of PLB (24-52) was incorporated into phospholipid bilayers prepared from 1-palmitoyl-2-oleoyl-sn-glycero-phosphocholine (POPC). Solid-state (31)P and (2)H NMR experiments were carried out to study the behavior of POPC bilayers in the presence of the hydrophobic peptide PLB at temperatures ranging from 30 degrees C to 60 degrees C. The PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 70 publications
4
53
0
Order By: Relevance
“…In particular, membrane association has been detected by using 2 H and 31 P solid-state NMR with cytoplasmic domain peptides and full-length versions of wt-PLN by the Middleton (19,20) and Lorigan (21,22) groups. The interactions with the membranes or membrane-mimicking systems induce a stable ␣-helical conformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, membrane association has been detected by using 2 H and 31 P solid-state NMR with cytoplasmic domain peptides and full-length versions of wt-PLN by the Middleton (19,20) and Lorigan (21,22) groups. The interactions with the membranes or membrane-mimicking systems induce a stable ␣-helical conformation.…”
Section: Discussionmentioning
confidence: 99%
“…This activity is relieved by phosphorylation of PLN at Ser-16 and/or Thr-17 and high calcium concentration within the cytosol. Wild-type PLN (wt-PLN) forms stable homopentamers in lipid bilayers and in detergent micelles, where each monomer is composed of a helical cytoplasmic domain (residues 1-16), a semiflexible loop (residues [17][18][19][20][21], and a helical transmembrane domain (residues 22-52) (1, 2). Mutagenesis, molecular biology, and in vivo studies revealed that the PLN pentamer depolymerizes into active monomers that bind and inhibit SERCA (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…42 The order parameters were a little smaller than those for the pure POPC_d 31 / cholesterol bilayers, which means that the insertion of the peptides into the bilayers enables the acyl chains to move more freely than in the POPC_d 31 bilayer/cholesterol bilayers.…”
Section: Resultsmentioning
confidence: 93%
“…2). Phospholamban is a transmembrane peptide that regulates cardiac contractility and spans the lipid bilayer [15,16]. (KIGAKI) 3 is a positively charged peptide designed to have high antimicrobial activity and is known to strongly interact with the membrane surface [1,17].…”
Section: Resultsmentioning
confidence: 99%